Implementasi STEAM Pada Kegiatan Proyek Pembuatan Lampu Lalu lintas Untuk Anak Usia 5-6 Tahun - Delia Nurlina; Dindin Abdul Muiz Lidinilah; Qonita Qonita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
The STEAM (Science, Technology, Engineering, Art, and Mathematics) approach is an educational innovation that offers early childhood learners experiences through activities integrating various disciplines. However, the implementation of STEAM elements within project-based activities relevant to children's daily lives requires further in-depth study. This research aims to describe the implementation of STEAM in a traffic light construction project for children aged 5–6 years. A descriptive qualitative approach was employed at TK PGRI Rancabogo. The subjects were children in